Emergence and Development of Tawjeeh al-Qira‟at - Abdelgelil, Mohamed Fathy Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
Tawjeeh al-Qira’at is a science which draws on shari’ah and Arabic studies. Likewise, it is a comprehensive field of study to which many branches of knowledge are related. However, some may think that it is not an independent or distinct field as it relates to Qur’an interpretation and grammar. This paper aims to trace the emergence of Tawjeeh al-Qira’at as a field of study and its evolution until it becomes an independent field of study. It also seeks to identify scholars who contributed to this science and those who have published books on it. The research adopted an analytical method through which the texts of Tawjeeh al-Qira’at were traced in the scientific literature, and concluded that Tawjeeh al-Qira’at has existed since the revelation of the Noble Qur’an. The research concluded that Tawjeeh al-Qira’at was an established field of study which draws heavily on Arabic grammar and Qur’an exegeses. The research also found that Harun bin al-A’war was the first author in this field of study through his book “Wujuh al-Qira’at” (Modes of Recitation).